2007
DOI: 10.1177/1533317507302071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multimodal Rehabilitative Intervention on Demented Patients and Their Caregivers

Abstract: Alzheimer's disease is becoming a social, political, and economic issue as a result of both the growing number of people affected and the enormous economic, social, and emotional costs involved in caring for Alzheimer's patients. The aim of this study is to evaluate the effects of a multimodal intervention program for patients with Alzheimer's disease and their caregivers. The study was conducted on a sample of 32 subjects: 16 Alzheimer's patients and their caregivers. The results obtained after the multimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
82
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 46 publications
0
82
0
7
Order By: Relevance
“…Positive emotions, enjoyment, creativity, belief, even spirituality can contribute to cognition as much as exercise and diet for example. Onor et al (2007) reported that socialization itself can lead to improvements, and 'programs that take a more holistic approach to the individual are more effective than those focusing on cognitive rehabilitation alone' (p. 270). Maci et al (2012) echoed this with their integrated approach of CS, physical activity and socialisation to slow down affective decline and reduce carer burden.…”
Section: Discussionmentioning
confidence: 99%
“…Positive emotions, enjoyment, creativity, belief, even spirituality can contribute to cognition as much as exercise and diet for example. Onor et al (2007) reported that socialization itself can lead to improvements, and 'programs that take a more holistic approach to the individual are more effective than those focusing on cognitive rehabilitation alone' (p. 270). Maci et al (2012) echoed this with their integrated approach of CS, physical activity and socialisation to slow down affective decline and reduce carer burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by an inability to carryout everyday tasks. Many individuals with AD commonly exhibit other behaviors such as agitation, aggression, or wandering (5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…The absence of significant differences in quality of life self-reported by CIND patients could be related with a better stability in the social life, a different situation that that lived by patients with mild AD. Onor and colleagues 36 reported that during the rehabilitation program, AD patients increased their socialization and created a network of alliances and mutual help.…”
Section: Discussionmentioning
confidence: 99%